Gwarancje ubezpieczeniowe jako instrumenty ochrony ekonomicznej przedsiębiorstw sektora budownictwa przy spadku stóp procentowych a ryzyko ubezpieczycieli w latach 2000-2005 - Solski, Tomasz (Wydawnictwo Akademii Ekonomicznej im. Oskara Langego we Wrocławiu, 2005)
The goal of this paper is to show the role of the insurance bonds (tender bond, performance bond, advance payment bond, maintenance bond) as the financial instruments that permit to lower the business costs, improve the fluidity and, very often, the survival of the construction industry companies during a slump in this sector in the years 2000-2005. Analysed is the profitability of the usage of the insurance bonds in relation to the decreasing interest rates by comparing the costs of such bonds to the costs of bank loans. Underlined are the factors that increase the risk for the insurers who offer the insurance bonds and the aspects of risk assessment in this regard. (original abstract)
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2005; nr 1088, t. 2, s. 245-253